Russian Internet News Sites, 2008–2018: Fostering an Informed Citizenry? - Rutger von Seth (Journal of Eurasian Studies, 2025)
Since Perestroika, Russian journalism has gone through a liberalization. However, the short lived apex of journalistic freedom that took place in the late 1980s and early 1990s was followed by a setback in particular since Putin’s accession to power in 2000. The situation for the freedom of the daily press has stagnated. Despite this, the findings based on qualitative text analysis of news articles in some of the most important Russian news sites, strongly indicate that during 2008–2018 readers of news sites were being addressed as active and knowledgeable citizens. The methods focussing on perspectivation and the use of sources, exploring what voices that are used to get messages through and how they are represented, are applied to four case studies casting light on the period. The findings imply that a number of Russian Internet outlets had strengthened their role as advocates of the Fourth Estate. The results further indicate a sharp distinction between news sites that are utilizing traditional Western journalistic devices, and news sites employing a traditional Russian/Soviet journalistic approach. Thus, the roles of the audiences as active citizens were to a certain extent strengthened.